Poisoning with methanol and carbamates. - Oom, Paulo (2002)
We describe the case of a eleven years old boy with a simultaneous intentional poisoning with methanol and carbamates. The symptomatology was biphasic due to the addition of the symptomatology of both intoxications. Therapeutic measures included gastrointestinal decontamination, sodium bicarbonate, atropine, ethanol administration and hemodialysis.